Exploring the Urban Model : Employment, Housing, and Infrastructure - Sturm, Daniel M.; Takeda, Kohei; Venables, Anthony J. (World Bank, Washington, DC, 2022)
The paper explores the properties of a modern urban model in which households’ and firms’ locations in the city are endogenously determined as functions of technology, preferences, and geography. This class of model provides insights into the factors that determine the shape and growth of cities. The paper increases understanding by studying the comparative static properties of the model, the effects of various policy interventions, and the circumstances under which different possible city types (mono- versus poly-centric) arise. It is a step to tailoring model structure to adequately describe real world cities of different sizes and types.